Alias - Bendis, Brian Michael 1967- (Marvel Worldwide, Inc., 2014)
"Meet Jessica Jones. Once upon a time she was a costumed super hero; now, she's the owner and sole employee of Alias Investigations--a small, private investigative firm specializing in superhuman cases. Jessica's life become expendable when she uncovers the potentially explosive secret of one hero's true identity. But her wit, charm and intelligence just may help her survive through another day. Thrust into the midst of a conspiracy that reaches the highest levels, has Jessica burned too many bridges to turn to old friends for help? Plus: Jessica travels to upstate New York to investigate the disappearance of a teenage girl rumored to be a mutant in a prejudiced small town; goes on a date with the Astonishing Ant Man ; teams up with Jessica Drew, the original Spider-Woman; and confronts the demons of her past!" -- Unedited summary from the book
"Alias created by Brian Michael Bendis.". - "Contains material originally published in magazine form as Alias #1-28 and What if Jessica Jones had joined the Avengers?". - "MAX omnibus"--Spine. - "Explicit content"--Cover
Keywords: Superheroes / Comic books, strips, etc; Women private investigators / Comic books, strips, etc; Detektivin; Superheldin; Comic